2022
DOI: 10.1016/j.resp.2022.103842
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive ventilation and high-flow nasal cannula in patients with acute hypoxemic respiratory failure by covid-19: A retrospective study of the feasibility, safety and outcomes

Abstract: Background Noninvasive ventilation (NIV) and High-flow nasal cannula (HFNC) are the main forms of treatment for acute respiratory failure. This study aimed to evaluate the effect, safety, and applicability of the NIV and HFNC in patients with acute hypoxemic respiratory failure (AHRF) caused by COVID-19. Methods In this retrospective study, we monitored the effect of NIV and HFNC on the SpO 2 and respiratory rate before, during, and after trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 38 publications
(57 reference statements)
0
32
0
Order By: Relevance
“…After excluding duplicates and evaluating the full texts of articles, we identified 23 eligible studies 9 , 11 32 (3 RCTs, 20 , 24 , 26 8 prospective observational studies, 13 , 16 , 18 , 19 , 22 , 25 , 28 , 30 and 12 retrospective observational studies). 9 , 11 , 12 , 14 , 15 , 17 , 21 , 23 , 27 , 29 , 31 , 32 The process of searching and screening is described in Figure 1 . The main characteristics of the articles included in the meta-analysis are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After excluding duplicates and evaluating the full texts of articles, we identified 23 eligible studies 9 , 11 32 (3 RCTs, 20 , 24 , 26 8 prospective observational studies, 13 , 16 , 18 , 19 , 22 , 25 , 28 , 30 and 12 retrospective observational studies). 9 , 11 , 12 , 14 , 15 , 17 , 21 , 23 , 27 , 29 , 31 , 32 The process of searching and screening is described in Figure 1 . The main characteristics of the articles included in the meta-analysis are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were considered to have an unclear risk of bias. The 20 observational 9 , 11 19 , 21 23 , 25 , 27 32 studies were assessed using the NOS checklist, and the results are shown in the Table 2 . All studies were of medium quality (⩾5 stars) or above, and 10 were considered high quality (⩾8 stars).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations